Impact of Migration on the Livelihood of Migrant Families: Cases from the Karnali Province - Ban, Padam; Gangal, Meenu (NPRC Journal of Multidisciplinary Research, 2025)
Migration is a natural phenomenon that occurs due to different reasons like jobs, businesses, education, and other physical facilities. Rural to urban migration is very high in the Nepalese context so this study aims to explore the impact of migration on the livelihood of migrant families in the case of Karnali province. The study was conducted among 196 migrant families who migrated from different parts of rural areas at the headquarters of Karnali province, Birendranagar Municipality of Surkhet district. The simple random sampling technique was adopted to select the migrant family. The result shows significant changes (before migration mean = 22.8, and after migration mean = 27.44 with p = .000) in the livelihood of migrant families after migration. Migration has markedly improved various facets of migrant families' lives, including livelihood, financial stability, social conditions, and access to essential services like education and healthcare, leading to enhanced overall quality of life and happiness. To sustain these positive outcomes, policymakers should support migration policies that offer better opportunities and services for migrant families, while also providing targeted assistance for vulnerable groups. Continuous monitoring and evaluation are essential to ensuring the long-term success of migration initiatives.